Ensino-Aprendizagem dos alunos surdos: o papel da formação docente de Ciências Biológicas no processo de inclusão. - Lima, Bárbara Felix de (Universidade Federal de São Carlos, 2023)
Herein we highlight the role of the initial training of Biological Sciences teachers in the teaching-learning process of deaf students, and proposes to analyze the social and historical context in that the education of these students was built, as well as explore, at national level, the idealization and practices involved in special education and inclusive education. Over this course, teacher training and science teaching were also investigated. For this purpose, the methodology used was bibliographic research in three digital libraries, namely: the Brazilian Digital Library of Theses and Dissertations (BDTD), the Scientific Electronic Library Online (SciELO), and the Portal of Periodicals of CAPES. From this survey, SciELO was the only bank of scientific productions that did not present a return, totaling 23 analyzed works, including theses, dissertations, and articles. Through the study, it can be inferred that the current academic training of teachers of biology graduates is not enough to face the challenges involved in science teaching for the deaf in basic education. Making it necessary to employ efficient legislation and invest in technical and pedagogical improvements, as well as to promote the funding of research in the area and the dissemination of materials produced in the academic environment. It is evident the indispensability of effective deaf individuals and their communities as protagonists of their schooling from the perspective of inclusion.
Teaching-Learning of deaf students: the role of Biological Sciences teacher training in the inclusion process
Keywords: Surdez; Docência; Formação Inicial; Ensino-aprendizagem; Inclusão; Deafness; Teaching; Initial Training; Teaching-learning; Inclusion; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO